2017
DOI: 10.18632/oncotarget.15614
|View full text |Cite
|
Sign up to set email alerts
|

Verteporfin exhibits YAP-independent anti-proliferative and cytotoxic effects in endometrial cancer cells

Abstract: Endometrial Carcinoma (EMCA) is the most common gynecologic malignancy and the fourth most common malignancy in women in the United States. Yes-associated protein (YAP) is a potent transcription coactivator acting via binding to the TEAD transcription factor, and plays a critical role in organ size regulation. Verteporfin (VP), a benzoporphyrin derivative, was identified as an inhibitor of YAP-TEAD interaction. We investigated the therapeutic efficacy and mechanism of VP in EMCA. The efficacy of VP on cell via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 34 publications
(44 reference statements)
9
75
0
Order By: Relevance
“…It has been reported that Verteporfin inhibited the interaction of YAP with TEAD, which, in turn, blocked transcriptional activation of target downstream of YAP, resulting in suppression of proliferation of several types of cancer cells 38 and tumor growth of PC-3 cells. 39 In contrast, other studies have indicated that inhibition of cell proliferation by Verteporfin in endometrial cancer cells 40 and colorectal cancer cells 41 are independent on YAP1. Our results suggest that inhibition of p62, Nrf2, Bcl-2, and Bcl-xL in PC-3 cells by…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that Verteporfin inhibited the interaction of YAP with TEAD, which, in turn, blocked transcriptional activation of target downstream of YAP, resulting in suppression of proliferation of several types of cancer cells 38 and tumor growth of PC-3 cells. 39 In contrast, other studies have indicated that inhibition of cell proliferation by Verteporfin in endometrial cancer cells 40 and colorectal cancer cells 41 are independent on YAP1. Our results suggest that inhibition of p62, Nrf2, Bcl-2, and Bcl-xL in PC-3 cells by…”
Section: Discussionmentioning
confidence: 83%
“…Histological staining of tumors and experiments in cancer cell lines have implicated YAP/TAZ in several other solid tumor types, including ovarian, [ 120–127 ] prostate, [ 128–134 ] bladder, [ 135–139 ] endometrial, [ 140,141 ] kidney, [ 142–144 ] thyroid, [ 145–149 ] adrenal, [ 150 ] mesothelioma, [ 151,152 ] sarcomas, [ 153–156 ] and epithelioid hemangioendothelioma. [ 157,158 ] In all the above cases, genetically engineered mouse models are still necessary to establish the causative role of Yap/Taz in these tumors in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Verteporfin was the first characterized YAP‐TEAD binding inhibitor, [ 283 ] but this compound suffers from low potency in vivo. [ 59,122,135,138,141 ] Thus, it will be of great interest to develop new and more potent inhibitors of this binding interaction, and the compound flufenamic acid is the first of a new wave of such small molecules. [ 284,285 ]…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted by Hodgkinson, Kruger, Mokwena, and Abrahamse () used the LDH assay to evaluate cell viability of cervical cancer cells (HeLa) against photodynamic therapy. A study carried out by Dasari et al () to assess anticancer effects of verteporfin in endometrial cancer cells (HEC‐1‐A and HEC‐1‐B), the LDH assay was used as a cell viability assay. The Promega Corporation also provides sensitive fluorescence‐based cell viability assays based on two different peptide substrates (GF‐AFC and bis‐AAF‐R110) as markers to detect viable and non‐viable cells.…”
Section: Cell Viability/cytotoxicity and Antiproliferative Assaysmentioning
confidence: 99%
“…A study carried out by Dasari et al (2017) to assess anticancer effects of verteporfin in endometrial cancer cells (HEC-1-A and HEC-1-B), the LDH assay was used as a cell viability assay. The Promega Corporation also provides sensitive fluorescence-based cell viability assays based on two different peptide substrates (GF-AFC and bis-AAF-R110) as markers to detect viable and non-viable cells.…”
Section: Introductionmentioning
confidence: 99%